Blood of hercules ebook - Mas, Jasmine (Villains of Lore, 2024)
The INSTANT New York Times bestseller! The overnight viral sensation everyone is talking about, Blood of Hercules, is a sarcastically funny, dark fantasy romance reimagining of Hercules from bestselling author Jasmine Mas—now available in paperback with full color character art, bonus content, and embossed lettering. I'm just a girl. And it turns out, I'm Hercules. I'm struggling to survive in a Titan infested world where Spartans, immortals from twelve royal families who have god-like powers and obscene wealth, rule over all. A shy-stammering foster child with nothing, I keep my head down, cover my scars, and focus on excelling in school. At least, I try to. Then it happens. My blood test reveals I'm part of the powerful elite. I'm one of them. A Spartan. Forced to attend the Spartan War Academy, I undergo the most harrowing test of all time to see if I have what it takes to be an immortal. There's just a few problems. Achilles and Patro are my scary mentors. Kharon, the ferryman of death, and Augustus, the son of war, are my terrifying professors. Also, I'm pretty sure either someone's stalking me everywhere I go, or my sanity's slipping––I have a bad feeling both are true. I'm surrounded by Villains and they're smothering me with their hate, obsession, and dark possessiveness. Too bad for them, they have no clue just who they're messing with. A Dark Romantasy for readers who love: "Who did this to you?" Why Choose Romance Extreme Enemies to Lovers Morally Gray Alpha Heroes Zodiac Academy, Quicksilver and When the Moon Hatched